Evaluasi Pengalaman Pengguna Aplikasi PLN Mobile Menggunakan Metode User Experience Questionnaire Plus (UEQ+) - Zulpa Salsabila; Fandi Halim; Viviyanty; Regina Ave Rameyana Berutu; Jekson Tua Sinamo (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
This research aims to explain the User Experience Questionnaire Plus (UEQ+) Method for Analyzing and Evaluating User Experience on the PLN Mobile Application. PLN Mobile is an online-based PLN application that has been downloaded by 10 million users until research was conducted from 10 May 2023 – 06 June 2023. The results of the PLN Mobile review received positive scores as well as negative reviews. Seeing positive and negative comments by application users, this prompted this research. This research is aimed at obtaining the level of user experience using scientific methods. This research will use the User Experience Questionnaire Plus (UEQ+) method which consists of 8 UEQ+ and also uses Microsoft Excel to analyze the questionnaire data obtained. As an online questionnaire, the scale that will be used in UEQ+ is in accordance with the relevant scale recommendations in the web shop product category. Based on the results of data processing from 404 respondents on each scale, the PLN Mobile application received a positive evaluation value on the scale (intuitive use, dependability, trust, content appropriateness, content quality, clarity, visual aesthetics, value) and received a mean value (1.94, 1.94, 2.03, 2.14, 2.11, 2.12, 2.01, 2.09). The results of all the important rating graph values ​​get positive values. This shows that every scale measured in the PLN Mobile application is important.